A rare earth element-doped composite phase change material and a preparation method thereof

CN120484783BActive Publication Date: 2026-10-20JIANGSU JINHE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510589216.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-08
Publication Date
2026-10-20
Estimated Expiration
2045-05-08

AI Technical Summary

Technical Problem

然而,现有技术主要集中于提升单一性能(如潜热或发光效率),对材料在复杂工况下的长期性能和多功能集成研究仍显不足,尤其是在反复热循环下的机械与化学稳定性问题尚未得到充分解决

Benefits of technology

[0017]本发明提供的稀土元素掺杂复合相变材料及其制备方法具有显著的有益效果。通过引入硝酸钇与硝酸镝共掺杂的稀土纳米颗粒(摩尔比95:5至95:15),结合含双硫键的聚氨酯自修复聚合物和三聚氰胺-甲醛树脂微胶囊化技术,材料展现出优异的潜热容量(175-182J/g)、高热导率(0.40-0.46W/(m·K))、卓越的机械强度(11.8-12.5MPa)和出色的热循环稳定性(93-96%保留率,1000次循环)。稀土掺杂增强了热学和光学性能,微胶囊化有效防止相变材料泄漏和相分离,自修复聚合物提高了长期机械耐久性。这些特性使材料在建筑节能、电子器件热管理和智能器件等领域具有广阔的应用前景,显著优于传统相变材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005392692150000101
    Figure BDA0005392692150000101
  • Figure BDA0005392692150000111
    Figure BDA0005392692150000111
Patent Text Reader

Abstract

The application discloses a kind of rare earth element doped composite phase change material and preparation method thereof.Preparation method includes: yttrium nitrate is mixed with dysprosium nitrate solution, pH is adjusted to 10, and rare earth doped nanoparticles are prepared by heating precipitation;Polyurethane prepolymer is dissolved with rare earth complex compound in dimethylformamide, and stirred to form a homogeneous solution;Melted paraffin wax is added with nanoparticles and surfactant, and dispersed by ultrasonic wave;The mixture is mixed with double-sulfur bond-containing polyurethane solution, and a precursor is formed by adding a crosslinking agent;Finally, the composite material is prepared by melamine-formaldehyde resin microencapsulation.The latent heat capacity of the material reaches 175-182 J / g, the thermal conductivity is 0.40-0.46 W / (m·K), the mechanical strength is 11.8-12.5 MPa, and the thermal cycle stability is 93-96%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of composite phase change materials, and in particular to a rare earth element-doped composite phase change material and its preparation method. Background Technology

[0002] Phase change materials (PCMs) have been widely used in building energy conservation, electronic device thermal management, solar energy utilization, and textiles due to their excellent performance in thermal energy storage and management. Rare earth element-doped PCMs have attracted much attention because they combine thermal energy storage and optical functions. In recent years, with the development of materials science, researchers have been exploring the use of rare earth elements (such as Eu) in PCMs. 3+ 、Tb 3+ Yb 3+ The latent heat storage capacity and optical properties of phase change materials (PCMs) have been significantly enhanced by combining them with nanostructures (such as metal-organic frameworks and nanoparticles). For example, rare-earth-doped composite PCMs have achieved dual-function applications of thermo-optics through upconversion or downconversion luminescence mechanisms, expanding their potential in sensors and smart devices. Furthermore, advancements in preparation methods such as microencapsulation, nanocomposite technology, and interface optimization have further improved the thermal conductivity and phase transition stability of PCMs. However, current technologies mainly focus on improving single properties (such as latent heat or luminescence efficiency), and research on the long-term performance and multifunctional integration of materials under complex operating conditions remains insufficient, especially regarding the mechanical and chemical stability under repeated thermal cycling, which has not yet been fully resolved.

[0003] Despite the significant technological advancements mentioned above, existing rare-earth-doped composite phase change materials still face several key technical bottlenecks in practical applications, particularly their susceptibility to mechanical degradation and phase separation during repeated thermal cycling, leading to a significant reduction in material lifespan. Specifically, organic phase change materials (such as paraffin and fatty acids) often develop microcracks or pores after multiple solid-liquid phase transitions due to molecular chain rearrangement or interfacial stress accumulation, reducing their mechanical strength; inorganic phase change materials (such as hydrated salts) suffer from a decline in latent heat efficiency due to phase separation or supercooling. Existing technologies attempt to alleviate these problems by adding reinforcing phases or optimizing encapsulation structures, but these methods often come at the cost of sacrificing thermal conductivity or latent heat capacity, and lack targeted solutions to the fundamental mechanisms of mechanical degradation (such as interfacial fatigue and molecular migration). Furthermore, the heterogeneous interfaces introduced by rare-earth doping may further exacerbate phase separation or stress concentration, especially under long-term thermal cycling, where uneven distribution of dopant elements may induce localized performance degradation. To address these shortcomings, this invention proposes a rare-earth-doped composite phase change material and its preparation method. Summary of the Invention

[0004] This application provides a method for preparing rare earth element-doped composite phase change materials, including the following technical steps:

[0005] Step S1. Mix yttrium nitrate with a rare earth precursor solution, adjust the pH to 10 to form a precipitate, heat and cool the mixture, and then centrifuge to separate the product to obtain rare earth doped nanoparticles.

[0006] Step S2. Add the polyurethane prepolymer and rare earth coordination compound to dimethylformamide and stir under a nitrogen atmosphere to form a homogeneous solution;

[0007] Step S3. Melt the phase change material, add rare earth-doped nanoparticles, disperse the nanoparticles using ultrasonic oscillation, and add a surfactant;

[0008] Step S4. Mix the phase change material and nanoparticle mixture with the self-healing polymer solution, add a crosslinking agent and continue stirring to form a viscous composite precursor;

[0009] Step S5. Mix melamine-formaldehyde resin with deionized water, adjust the pH to 4.5, and add the composite precursor dropwise to the shell-forming solution under high-speed stirring to form microcapsules.

[0010] In a preferred embodiment of a method for preparing a rare earth element-doped composite phase change material, in step S1, the rare earth precursor solution is a dysprosium nitrate solution, and the yttrium nitrate and dysprosium nitrate solution are mixed in a molar ratio of 95:5 to 95:15.

[0011] In a preferred embodiment of a method for preparing a rare earth element-doped composite phase change material, in step S2, the rare earth coordination compound is a chelate synthesized by coordination of LaCl3 and 2,2'-bipyridine.

[0012] In a preferred embodiment of a method for preparing a rare earth element-doped composite phase change material, in step S3, the rare earth-doped nanoparticles account for 2 wt% to 5 wt% of the phase change material.

[0013] In a preferred embodiment of a method for preparing a rare earth element-doped composite phase change material, in step S3, the phase change material is paraffin wax, and the surfactant is polysorbate, sodium dodecyl sulfate, or the surfactant accounts for 0.1% to 0.4% of the mass of the phase change material.

[0014] In a preferred embodiment of a method for preparing a rare earth element-doped composite phase change material, in step S4, the self-healing polymer is a polyurethane containing disulfide bonds, the crosslinking agent is hexamethylene diisocyanate, and the crosslinking agent accounts for 1 wt% to 2 wt% of the polyurethane containing disulfide bonds.

[0015] In a preferred technical solution for the preparation of a rare earth element-doped composite phase change material, in step S4, the phase change material-nanoparticle mixture is mixed with a polyurethane solution containing disulfide bonds at a mass ratio of 70:20 to 70:40.

[0016] In a preferred embodiment of a method for preparing a rare-earth element-doped composite phase change material, in step S5, the mass ratio of melamine-formaldehyde resin to deionized water is 1:5-1:10.

[0017] The rare-earth element-doped composite phase change materials and their preparation method provided by this invention have significant beneficial effects. By introducing rare-earth nanoparticles co-doped with yttrium nitrate and dysprosium nitrate (molar ratio 95:5 to 95:15), combined with a polyurethane self-healing polymer containing disulfide bonds and melamine-formaldehyde resin microencapsulation technology, the materials exhibit excellent latent heat capacity (175-182 J / g), high thermal conductivity (0.40-0.46 W / (m·K)), outstanding mechanical strength (11.8-12.5 MPa), and excellent thermal cycling stability (93-96% retention rate, 1000 cycles). Rare-earth doping enhances thermal and optical properties, microencapsulation effectively prevents leakage and phase separation of the phase change material, and the self-healing polymer improves long-term mechanical durability. These properties make the materials promising for applications in building energy conservation, thermal management of electronic devices, and smart devices, significantly superior to traditional phase change materials. Detailed Implementation

[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0019] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single embodiment or an embodiment selectively excluded from other embodiments.

[0021] Example

[0022] Example 1

[0023] Example 1 provides a method for preparing rare earth element-doped composite phase change materials, including the following technical steps:

[0024] Step S1. Mix yttrium nitrate and dysprosium nitrate solutions at a molar ratio of 95:5, add 1 mol / L sodium hydroxide dropwise, adjust the pH to 10 to form a precipitate, transfer the mixture to a polytetrafluoroethylene-lined autoclave, heat at 200°C for 10 hours, cool, centrifuge to separate the product, wash with ethanol and deionized water, and dry at 80°C for 6 hours to obtain rare earth-doped nanoparticles;

[0025] Step S2. Dissolve the polyurethane prepolymer and rare earth coordination compound in dimethylformamide (DMF) at a mass ratio of 2:1. The rare earth coordination compound is a chelate synthesized by coordination of LaCl3 and 2,2'-bipyridine. Stir at 60°C for 2 hours under a nitrogen atmosphere to form a homogeneous solution.

[0026] Step S3. Melt paraffin at 70°C, add rare earth-doped nanoparticles accounting for 5 wt% of the paraffin mass, disperse the nanoparticles for 30 minutes using ultrasonic oscillation (frequency: 20 kHz, power: 150 W, time: 30 minutes), maintain the temperature at 70°C, and add 0.1 wt% polysorbate.

[0027] Step S4. Mix the phase change material-nanoparticle mixture with the polyurethane solution containing disulfide bonds at a mass ratio of 70:30, stir at 500 rpm for 1 hour at 60°C to achieve homogeneity, add 1 wt% of crosslinking agent (such as hexamethylene diisocyanate) of the polyurethane containing disulfide bonds to initiate polymerization, and continue stirring for 30 minutes to form a viscous composite precursor.

[0028] Step S5. Melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:10. The pH is adjusted to 4.5 with acetic acid. The composite precursor is added dropwise to the shell formation solution under high-speed stirring at 55°C and 1000 rpm. The reaction is continued for 3 hours to form microcapsules.

[0029] Example 2

[0030] Example 2 provides a method for preparing rare earth element-doped composite phase change materials, including the following technical steps:

[0031] Step S1. Mix yttrium nitrate and dysprosium nitrate solutions at a molar ratio of 95:15, add 1 mol / L sodium hydroxide dropwise, adjust the pH to 10 to form a precipitate, transfer the mixture to a polytetrafluoroethylene-lined autoclave, heat at 150°C for 8 hours, cool, centrifuge to separate the product, wash with ethanol and deionized water, and dry at 80°C for 6 hours to obtain rare earth-doped nanoparticles;

[0032] Step S2. Dissolve the polyurethane prepolymer and rare earth coordination compound in dimethylformamide (DMF) at a mass ratio of 1:1. The rare earth coordination compound is a chelate synthesized by coordination of LaCl3 and 2,2'-bipyridine. Stir at 60°C for 2 hours under a nitrogen atmosphere to form a homogeneous solution.

[0033] Step S3. Melt paraffin at 70°C, add rare earth-doped nanoparticles accounting for 2 wt% of the paraffin mass, disperse the nanoparticles for 30 minutes using ultrasonic oscillation (frequency: 40 kHz, power: 100 W, time: 10 minutes), keep the temperature at 70°C, and add sodium dodecyl sulfate accounting for 0.4 wt% of the paraffin mass.

[0034] Step S4. Mix the phase change material-nanoparticle mixture with a polyurethane solution containing disulfide bonds at a mass ratio of 70:40, stir at 500 rpm for 1 hour at 60°C to achieve homogeneity, add 2 wt% of crosslinking agent (such as hexamethylene diisocyanate) to the polyurethane solution containing disulfide bonds to initiate polymerization, and continue stirring for 30 minutes to form a viscous composite precursor.

[0035] Step S5. Melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:10. The pH is adjusted to 4.5 with acetic acid. The composite precursor is added dropwise to the shell formation solution under high-speed stirring at 55°C and 2000 rpm. The reaction is continued for 3 hours to form microcapsules.

[0036] Example 3

[0037] Example 3 provides a method for preparing rare earth element-doped composite phase change materials, including the following technical steps:

[0038] Step S1. Mix yttrium nitrate and dysprosium nitrate solutions at a molar ratio of 95:8, add 1 mol / L sodium hydroxide dropwise to adjust the pH to 10, and form a precipitate. Transfer the mixture to a polytetrafluoroethylene-lined autoclave, heat at 150°C for 15 hours, cool, centrifuge to separate the product, wash with ethanol and deionized water, and dry at 80°C for 8 hours to obtain rare earth-doped nanoparticles.

[0039] Step S2. Dissolve the polyurethane prepolymer and rare earth coordination compound in dimethylformamide (DMF) at a mass ratio of 2:1. The rare earth coordination compound is a chelate synthesized by coordination of LaCl3 and 2,2'-bipyridine. Stir at 60°C for 2 hours under a nitrogen atmosphere to form a homogeneous solution.

[0040] Step S3. Melt paraffin at 70°C, add 2wt% rare earth-doped nanoparticles, disperse the nanoparticles using ultrasonic oscillation (frequency: 40kHz, power: 100W, time: 10 minutes) for 30 minutes, keep the temperature at 70°C, and add 0.3wt% polyvinylpyrrolidone.

[0041] Step S4. Mix the phase change material-nanoparticle mixture with a polyurethane solution containing disulfide bonds at a mass ratio of 70:30, stir at 500 rpm for 1 hour at 60°C to achieve homogeneity, add 2 wt% of crosslinking agent (such as hexamethylene diisocyanate) to the polyurethane solution containing disulfide bonds to initiate polymerization, and continue stirring for 30 minutes to form a viscous composite precursor.

[0042] Step S5. Melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:8. The pH is adjusted to 4.5 with acetic acid. The composite precursor is added dropwise to the shell formation solution under high-speed stirring at 55°C and 1500 rpm. The reaction is continued for 3 hours to form microcapsules.

[0043] Example 4

[0044] Example 4 provides a method for preparing rare earth element-doped composite phase change materials, including the following technical steps:

[0045] Step S1. Mix yttrium nitrate and dysprosium nitrate solutions at a molar ratio of 95:10, add 1 mol / L sodium hydroxide dropwise to adjust the pH to 10, and form a precipitate. Transfer the mixture to a polytetrafluoroethylene-lined autoclave, heat at 180°C for 15 hours, cool, centrifuge to separate the product, wash with ethanol and deionized water, and dry at 80°C for 8 hours to obtain rare earth-doped nanoparticles.

[0046] Step S2. Dissolve the polyurethane prepolymer and rare earth coordination compound in dimethylformamide (DMF) at a mass ratio of 3:1. The rare earth coordination compound is a chelate synthesized by coordination of LaCl3 and 2,2'-bipyridine. Stir at 60°C for 2 hours under a nitrogen atmosphere to form a homogeneous solution.

[0047] Step S3. Melt paraffin at 70°C, add rare earth-doped nanoparticles accounting for 5 wt% of the paraffin mass, disperse the nanoparticles for 30 minutes using ultrasonic oscillation (frequency: 40 kHz, power: 100 W, time: 10 minutes), keep the temperature at 70°C, and add polyvinylpyrrolidone accounting for 0.4 wt% of the paraffin mass.

[0048] Step S4. Mix the phase change material-nanoparticle mixture with a polyurethane solution containing disulfide bonds at a mass ratio of 70:30, stir at 500 rpm for 1 hour at 60°C to achieve homogeneity, add 1 wt% of crosslinking agent (such as hexamethylene diisocyanate) to the polyurethane solution containing disulfide bonds to initiate polymerization, and continue stirring for 30 minutes to form a viscous composite precursor.

[0049] Step S5. Melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:10. The pH is adjusted to 4.5 with acetic acid. The composite precursor is added dropwise to the shell formation solution under high-speed stirring at 55°C and 1500 rpm. The reaction continues for 3 hours to form microcapsules.

[0050] Comparison Example

[0051] Comparison Example 1: Composite Phase Change Materials without Rare Earth Doped Nanoparticles

[0052] Step S1: Skip the preparation of rare earth-doped nanoparticles and proceed directly to step S2.

[0053] Step S2: Under the conditions of Example 1, the polyurethane prepolymer and rare earth coordination compound (LaCl3 and 2,2'-bipyridine chelate) were dissolved in dimethylformamide (DMF) at a mass ratio of 2:1, and stirred at 60°C for 2 hours under a nitrogen atmosphere to form a homogeneous solution.

[0054] Step S3: Melt paraffin at 70°C, add 0.1 wt% polysorbate as a surfactant (without rare earth doped nanoparticles), and stir until homogeneous.

[0055] Step S4: Mix paraffin wax and polyurethane solution containing disulfide bonds at a mass ratio of 70:30, stir at 500 rpm for 1 hour at 60°C, add 1 wt% hexamethylene diisocyanate as a crosslinking agent, and continue stirring for 30 minutes to form a viscous composite precursor.

[0056] Step S5: Melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:10. The pH is adjusted to 4.5 with acetic acid. The composite precursor is added dropwise to the shell formation solution under high-speed stirring at 55℃ and 1000rpm. The reaction is carried out for 3 hours to form microcapsules.

[0057] Compare with Example 2: Use ordinary polyurethane instead of polyurethane containing disulfide bonds.

[0058] Step S1: Under the conditions of Example 1, yttrium nitrate and dysprosium nitrate solutions were mixed at a molar ratio of 95:5, the pH was adjusted to 10, heated at 200°C for 10 hours, centrifuged, washed, and dried to obtain rare earth-doped nanoparticles.

[0059] Step S2: Same as in Example 1, dissolve the polyurethane prepolymer and rare earth coordination compound (LaCl3 and 2,2'-bipyridine chelate) in DMF at a mass ratio of 2:1, and stir at 60°C for 2 hours under a nitrogen atmosphere.

[0060] Step S3: Melt paraffin at 70°C, add 5wt% rare earth-doped nanoparticles, ultrasonically vibrate (20kHz, 150W, 30 minutes), and add 0.1wt% polysorbate.

[0061] Step S4: Mix the phase change material-nanoparticle mixture with a common polyurethane solution (without disulfide bonds) at a mass ratio of 70:30, stir at 500 rpm for 1 hour at 60°C, add 1 wt% hexamethylene diisocyanate, and continue stirring for 30 minutes to form a composite precursor.

[0062] Step S5: Same as in Example 1, melamine-formaldehyde resin and deionized water are mixed at a mass ratio of 1:10, pH is adjusted to 4.5, stirred at 55°C and 1000 rpm, and the precursor is added dropwise. The reaction is carried out for 3 hours to form microcapsules.

[0063] Comparison Example 3: No microencapsulation treatment performed

[0064] Steps S1-S4: Prepare according to the steps of Example 1, that is, prepare rare earth doped nanoparticles, rare earth coordination compound solution, phase change material-nanoparticle mixture, and mix with polyurethane solution containing disulfide bonds to form a composite precursor.

[0065] Step S5: Omit the microencapsulation step and directly vacuum dry the composite precursor obtained in step S4 at 60°C for 6 hours to obtain a solid composite phase change material.

[0066] Compare with Example 4: Using a single rare earth element (without dysprosium nitrate doping)

[0067] Step S1: Using only yttrium nitrate solution (without dysprosium nitrate), add 1 mol / L sodium hydroxide dropwise to adjust the pH to 10, heat at 200℃ for 10 hours, centrifuge, wash, and dry at 80℃ for 6 hours to obtain single rare earth (yttrium) nanoparticles.

[0068] Steps S2-S5: The steps are carried out exactly as described in Example 1, using rare earth coordination compounds, polyurethane containing disulfide bonds, microencapsulation, etc. The only difference is that in step S3, single rare earth (yttrium) nanoparticles (5wt%) are added.

[0069] Performance testing methods

[0070] 1. Latent heat capacity (ΔH): Measures the heat storage capacity of a material;

[0071] 2. Phase transition temperature (Tm): Reflects the operating temperature range of the material;

[0072] 3. Thermal conductivity (k): Affects heat transfer efficiency;

[0073] 4. Mechanical strength (σ): assesses the material's durability under repeated thermal cycling;

[0074] 5. Thermal cycling stability (ΔH retention): Evaluates the performance retention rate of a material after multiple thermal cycles;

[0075] Table 1

[0076]

[0077]

[0078] As can be seen from Examples 1 to 4 and Table 1, the latent heat capacity of the rare earth element-doped composite phase change materials in Examples 1 to 4 is 175-182 J / g, and the phase change temperature is...

[0079] With a temperature range of 54.8-55.2℃, a thermal conductivity of 0.40-0.46 W / (m·K), a mechanical strength of 11.8-12.5 MPa, and a thermal cycling stability of 93-96%, the synergistic effect of rare earth-doped nanoparticles (yttrium nitrate and dysprosium nitrate) and polyurethane containing disulfide bonds enhances the heat transfer efficiency and mechanical stability. Microencapsulation technology further improves the interfacial stability and resistance to thermal cycling degradation of the material.

[0080] As can be seen from Example 1, Comparative Example 1, and Table 1, the rare earth element-doped composite phase change material of Example 1 is superior to Comparative Example 1 in terms of latent heat capacity (180 J / g), phase change temperature (55.0 °C), thermal conductivity (0.45 W / (m·K)), mechanical strength (12.5 MPa), and thermal cycling stability (95%) (latent heat capacity 170 J / g, phase change temperature 54.5 °C, thermal conductivity 0.30 W / (m·K), mechanical strength 10.5 MPa, and thermal cycling stability 85%). Specifically, Example 1 has a latent heat capacity 10 J / g higher, thermal conductivity increased by 50%, mechanical strength increased by 19%, and thermal cycling stability increased by 10%. This is because Example 1 introduces rare earth-doped nanoparticles (yttrium nitrate and dysprosium nitrate in a 95:5 molar ratio), which enhance heat transfer efficiency and interfacial stability through ultrasonic dispersion and microencapsulation technology. The doping of rare earth elements also optimizes the thermal and optical properties of the material. In contrast, Comparative Example 1 omitted rare earth-doped nanoparticles, resulting in lower thermal conductivity and latent heat capacity. The lack of synergistic effect of rare earth elements significantly reduced mechanical strength and long-term thermal cycling stability.

[0081] Based on Example 1, Comparative Example 2, and Table 1, it can be seen that the rare-earth element-doped composite phase change material of Example 1 is superior to Comparative Example 2 in terms of latent heat capacity (180 J / g), phase change temperature (55.0℃), thermal conductivity (0.45 W / (m·K)), mechanical strength (12.5 MPa), and thermal cycling stability (95%) (latent heat capacity 176 J / g, phase change temperature 55.0℃, thermal conductivity 0.43 W / (m·K), mechanical strength 8.5 MPa, and thermal cycling stability 80%). This is because Example 1 uses polyurethane containing disulfide bonds as a self-healing polymer. Its dynamic chemical bonds can repair microcracks during thermal cycling, enhancing mechanical durability and interfacial stability. Furthermore, the rare-earth-doped nanoparticles (yttrium nitrate and dysprosium nitrate) further optimize heat transfer and structural stability. In contrast, Comparative Example 2 uses ordinary polyurethane, which lacks self-healing capabilities, resulting in a significant decrease in mechanical strength and thermal cycling stability. Although the thermal conductivity remains relatively high due to rare-earth doping, its overall performance is limited.

[0082] As can be seen from Example 1, Comparative Example 3, and Table 1, the rare earth element-doped composite phase change material of Example 1 is significantly superior to Comparative Example 3 (latent heat capacity 165 J / g, phase change temperature 54.7℃, thermal conductivity 0.38 W / (m·K)), mechanical strength 9.0 MPa, and thermal cycling stability 75%) in terms of latent heat capacity (180 J / g), phase change temperature 55.0℃, thermal conductivity 0.38 W / (m·K), mechanical strength 9.0 MPa, and thermal cycling stability 75%). Specifically, Example 1 has a latent heat capacity 15 J / g higher, thermal conductivity increased by 18.4%, mechanical strength increased by 38.9%, and thermal cycling stability increased by 26.7%. This is because Example 1 effectively encapsulates the phase change material and rare earth-doped nanoparticles through microencapsulation technology (melamine-formaldehyde resin shell), enhancing interfacial stability and resistance to phase separation. The self-healing properties of polyurethane containing disulfide bonds further improve the material's durability in thermal cycling. In contrast, Comparative Example 3 omitted the microencapsulation step, which led to leakage and phase separation of the phase change material during repeated thermal cycling, resulting in decreased dispersion stability of rare earth-doped nanoparticles and consequently significantly reduced latent heat capacity, thermal conductivity, mechanical strength, and thermal cycling stability.

[0083] Based on Example 1, Comparative Example 4, and Table 1, it can be seen that the rare earth element-doped composite phase change material of Example 1 is superior to Comparative Example 4 (latent heat capacity 178 J / g, phase change temperature 55.0℃, thermal conductivity 0.45 W / (m·K)), mechanical strength 12.5 MPa, and thermal cycling stability 95%) in terms of latent heat capacity (180 J / g), phase change temperature 55.0℃, thermal conductivity 0.35 W / (m·K), mechanical strength 11.5 MPa, and thermal cycling stability 90%). Specifically, Example 1 has a slightly higher latent heat capacity of 2 J / g, a significantly improved thermal conductivity of 28.6%, an increased mechanical strength of 8.7%, and improved thermal cycling stability of 5.6%. The reason lies in the fact that Example 1 used rare-earth nanoparticles co-doped with yttrium nitrate and dysprosium nitrate (95:5 molar ratio). The doping of dysprosium enhanced the thermal and optical properties of the material through a synergistic effect, improving thermal conductivity and structural stability. Furthermore, microencapsulation and the self-healing properties of the disulfide-bonded polyurethane further solidified long-term performance. In contrast, Control Example 4 used only a single rare-earth (yttrium) nanoparticle, lacking the synergistic effect of dysprosium, resulting in lower thermal conductivity. The singularity of the doping element limited interface optimization and thermal cycling stability, and the mechanical strength and latent heat capacity were also slightly inferior to Example 1.

[0084] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a rare earth element-doped composite phase change material, characterized in that, The process includes the following steps: Step S1. Yttrium nitrate is mixed with a rare earth precursor solution, the pH is adjusted to 10 to form a precipitate, the mixture is heated and cooled, and the product is separated by centrifugation to obtain rare earth-doped nanoparticles; wherein the rare earth precursor solution is a dysprosium nitrate solution, and the yttrium nitrate and dysprosium nitrate solutions are mixed in a molar ratio of 95:5 to 95:15; Step S2. A polyurethane prepolymer containing disulfide bonds and a rare earth coordination compound are added to dimethylformamide, and stirred under a nitrogen atmosphere to form a homogeneous solution of a self-healing polymer; wherein the rare earth coordination compound is a chelate synthesized by coordinating LaCl3 with 2,2′-bipyridine; Step S3. A phase change material is melted, the rare earth-doped nanoparticles are added, the rare earth-doped nanoparticles are dispersed by ultrasonic oscillation, and a surfactant is added; wherein the rare earth-doped nanoparticles account for 2 wt% to 5 wt% of the mass of the phase change material. The phase change material is paraffin wax, and the surfactant is polysorbate, sodium dodecyl sulfate, or polyvinylpyrrolidone, accounting for 0.1% to 0.4% of the mass of the phase change material; Step S4. Mix the mixture of the phase change material and rare earth-doped nanoparticles obtained in Step S3 with the homogeneous solution of the self-healing polymer obtained in Step S2, add a crosslinking agent and continue stirring to form a viscous composite precursor; wherein, the crosslinking agent is hexamethylene diisocyanate, and the crosslinking agent accounts for 1 wt% to 2 wt% of the mass of the polyurethane containing disulfide bonds; Step S5. Mix melamine-formaldehyde resin with deionized water, adjust the pH to 4.5, and add the composite precursor dropwise to the shell-forming solution under high-speed stirring to react and form microcapsules.

2. The method for preparing rare earth element-doped composite phase change materials according to claim 1, characterized in that, In step S4, the phase change material-rare earth doped nanoparticle mixture is mixed with the self-healing polymer homogeneous solution obtained in step S2 at a mass ratio of 70:20 to 70:

40.

3. The method for preparing rare earth element-doped composite phase change materials according to claim 1, characterized in that, In step S5, the mass ratio of the melamine-formaldehyde resin to deionized water is 1:5 to 1:10.

Citation Information

Patent Citations

  • Preparation method of nano particle-doped phase change microcapsule

    CN104962240A

  • Self-repairing polyurethane microcapsule as well as preparation method and application thereof

    CN119613666A